Finding Evidence of the Existence of Enterprise Risk Management In Non-Financial Industries: The Case of Shell Nigeria Ltd and ChevronTexaco Nigeria Ltd - Adesanya, Tolulope (2010)
This study explores the risk finance and risk transfer strategies of international oil companies operating in the Nigerian oil and gas industry in order to find out the extent to which Enterprise Risk Management (ERM) exists within them. ERM is considered by many to be the new risk management paradigm. The general consensus is that it is the superior risk management technique particularly in comparison with the traditional ‘silo’ approach. While the ‘silo’ approach is characterized by a compartmentalization of risks, ERM encourages integration of risks to be managed holistically within a unified framework. Existing literature on ERM is predominantly based on the financial services industry with very little reference to its implementation in non-financial industries. In light of this, this study was done to shed some light on the existence of ERM in one of such ‘non-financial’ industries, the Nigerian oil and gas industry. The study found that ERM as described does not exist in the operations of Shell and Chevron Nigeria. A reason for this finding may be that the ERM framework as defined is incompatible with the studied context. This could also explain why there is little literature on ERM in the context of non-financial services.